Analisis Hukum Islam terhadap Penggunaan Bitcoin dalam Transaksi Ekonomi Modern: Tinjauan Hukum Islam dan Perspektif Hukum Internasional - Saka Shofa'il Asroor (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Over the past 20 years, developments in digital technology have led to the emergence of financial innovation in the form of cryptocurrencies, with Bitcoin being the main pioneer. Bitcoin is a decentralized, blockchain-based electronic payment system that is not controlled by a single financial institution. Although its presence facilitates quick and straightforward cross-border transactions, it also raises ethical and legal issues, especially when taking into account Islamic law, which strongly emphasizes justice, certainty, and the welfare of society. This paper aims to investigate the usage of Bitcoin in modern economic transactions from the standpoint of Islamic and international law. This study investigates Islamic legal sources, the views of Islamic scholars, fatwas (religious decrees), and international laws and regulations pertaining to cryptocurrency assets using a qualitative, normative-empirical methodology. The results show that, although opinions among scholars differ, the usage of Bitcoin is subject to ijtihadiyah (Islamic ijtihad) in Islamic law. Some reject it because of its great volatility and speculative potential, while others allow it as long as it provides advantages and does not include riba, gharar, or maysir (the risks associated with gambling). In terms of international law, Bitcoin is typically seen as a digital asset that has to be closely watched in order to preserve economic stability and deter financial crime. Therefore, balanced legislation is required to guarantee that the usage of Bitcoin is in line with the principles of sharia maqasid and global economic fairness.